Farm odor treatment method

By using MgO sustained release materials and carbon-rich porous materials in the farm, the problems of odor removal and nitrogen resource recovery in the farm are solved, and efficient odor treatment and resource recycling are achieved.

CN119607830APending Publication Date: 2025-03-14CHONGQING ANIMAL HUSBANDRY TECH EXTENSION STATION
View PDF 0 Cites 1 Cited by

Patent Information

Application Number
CN202411936689.9
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-26
Publication Date
2025-03-14

AI Technical Summary

Technical Problem

The prior art has poor purification effect when dealing with odor in the farm, and directly discharges foul-odor gases to harm the environment and human health. The nitrogen loss caused by ammonia volatility is large, affecting the breeding benefits.

Method used

By preparing MgO sustained release materials and carbon-rich porous materials, fillers are put into the gas scrubber tower, and odor is treated with spraying and exhaust devices, so as to remove odor and recover nitrogen resources.

Benefits of technology

It effectively reduces the precipitation of struvite generated during odor treatment, ensures the continuous release of magnesium ions, improves the efficiency of odor treatment, and realizes the recycling of nitrogen and phosphorus during the breeding process, providing high-quality sustained-release fertilizer.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119607830A_ABST
    Figure CN119607830A_ABST
Patent Text Reader

Abstract

The invention discloses a treatment method of farm odor, and belongs to the technical field of farm odor treatment, the method comprises the following steps: (1) preparing an MgO sustained-release material; (2) preparing a carbon-rich porous material; (3) setting an odor treatment device; and (4) treating the odor: spraying the oxidized biogas slurry downwards from the top of the odor treatment device, then enabling the odor to enter from the bottom of the odor treatment device by utilizing an exhaust device, treating the odor and recycling nutrient resources, and solving the problem of recycling nitrogen resources in the breeding process while removing the odor of the farm.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of odor treatment in breeding farms, and in particular to a method for treating odor in breeding farms. Background Art

[0002] With the development of large-scale farms and the further improvement of environmental requirements, the deodorization of large-scale farms has become increasingly important. Odor pollution in farms is one of the types of farm pollution. The odor is mainly composed of ammonia, hydrogen sulfide, skatole, etc., mainly because of the action of microorganisms in the stacking process of farm manure, which produces a large amount of harmful and smelly gases. The odor will not only cause damage to animals in the farm and affect the benefits of the farm; it will also spread further, pollute the surrounding environment, and affect the health of nearby residents. Compared with wastes such as farm manure and sewage, the collection and treatment of odor is difficult, and the treatment technology is relatively weak. How to control and reduce odor throughout the entire breeding production process has gradually become the focus of pollution control in the breeding industry. At present, most farms usually use biological deodorizers on the ground, walls, roofs, and drainage ditches of poultry and livestock houses to inhibit the conversion of ammonia. For the generated odor, the odorous gas is discharged into the air through fans or other exhaust devices. However, the odor purification effect is not ideal, and directly emitting odorous gases into the air will cause harm to the environment and human health. The nitrogen loss caused by ammonia volatilization in the breeding process accounts for about 20% of the nitrogen input in the breeding process. Therefore, controlling ammonia volatilization in farms is of great significance to reducing ammonia emissions in farms. Odor can be converted into fertilizer to achieve the recycling of nitrogen resources, which not only reduces waste emissions, but also provides organic fertilizers required for agriculture and increases soil fertility.

[0003] Therefore, the present invention provides a method for treating farm odor, which solves the problem of removing farm odor and recycling nitrogen resources in the breeding process at the same time. Summary of the invention

[0004] In view of this, the purpose of the present invention is to provide a method for treating farm odor, which solves the problem of removing farm odor and recycling nitrogen resources in the breeding process at the same time.

[0005] The present invention solves the above technical problems by the following technical means:

[0006] A method for treating odor in a farm, the method comprising the following steps:

[0007] (1) Preparation of MgO slow-release material: The straw was crushed and mixed with MgCl2·6H2O solution, and then NaCO3 and NaOH were added to adjust the pH to 10. The mixture was stirred for 2 h in a stirrer and then allowed to stand for 1 day. The solid-liquid mixture was dried and ground again, extruded to obtain granules, and the granules were transferred to a biochar preparation machine and carbonized at 550°C for 2 h in the absence of oxygen. After cooling to room temperature, biochar granules were obtained. A polymer film was then loaded on the outside of the biochar granules to obtain MgO slow-release material.

[0008] (2) Preparation of carbon-rich porous materials: The material with high lignin content was crushed and sieved, and then dried at 100°C. It was then immersed in concentrated phosphoric acid at a mass ratio of 1:3 and dried again at 100°C. The dried high lignin material was pyrolyzed at 800°C for 2-3h, cooled to room temperature, and rinsed with deionized water until the filtrate was neutral to obtain a carbon-rich porous material.

[0009] (3) Setting up the odor treatment device: Filling the prepared MgO slow-release material and carbon-rich porous material into a scrubbing tower to obtain an odor treatment device;

[0010] (4) Odor treatment: The oxidized biogas slurry is sprayed down from the top of the odor treatment device, and then the odor is introduced into the bottom of the odor treatment device through the exhaust device for odor treatment. After the treatment, the filler is recovered.

[0011] Furthermore, the method of biochar loading polymer membrane in step (1) is as follows:

[0012] S1: adding polyvinyl alcohol to water, heating and stirring until completely dissolved to obtain a polyvinyl alcohol solution; adding stearic acid to anhydrous ethanol, heating and stirring until completely dissolved to obtain a stearic acid solution; mixing the polyvinyl alcohol solution and the stearic acid solution evenly, stirring at 85-90° C. for 2-3 h, then adding β-cyclodextrin, glucose, and 1wt% citric acid solution, stirring at 50-55° C. for 2-3 h, cooling to room temperature, and adjusting the pH to 6-6.5 to obtain a mixed solution;

[0013] S2: Evenly mix hydroxypropyl methylcellulose, polyethylene glycol, talc, titanium dioxide and the mixed solution to obtain a mixed material, mix the mixed material with anhydrous ethanol in a mass ratio of 1:40, stir with a magnetic stirrer at room temperature for 40-50 minutes, ultrasonicate at room temperature for 15-20 minutes, then mix it with biochar particles, dry it at 40-45°C for 5-6 hours and take it out.

[0014] Furthermore, in the method of loading the biochar onto the polymer membrane, the mass ratio of hydroxypropyl methylcellulose, polyvinyl alcohol, polyethylene glycol, talc and titanium dioxide is (30-32):(20-22):(8-10):(7-8):(25-28).

[0015] Furthermore, in step S1 of the method for loading polymer membrane with biochar, the mass ratio of polyvinyl alcohol, stearic acid, β-cyclodextrin, glucose and 1 wt% citric acid solution is (5-6): (1-1.2): (2.5-3): (1-1.3): (10-15).

[0016] Furthermore, in step (1), the crop straw is crushed to a particle size of less than 0.25 mm, and the crushed crop straw and MgCl2·6H2O are mixed in a volume-to-mass ratio of 1 kg:10 L.

[0017] Furthermore, in step (1), the compression molding obtains particles with a particle size of 1-1.5 cm.

[0018] Furthermore, in step (3), the filler is composed of two layers, the upper layer of the filler is MgO slow-release material, accounting for 10-20% of the total thickness of the filler, and the lower layer of the filler is a mixture of MgO slow-release material and carbon-rich porous material in a mass ratio of (2-3): 10, and the filler height is usually 0.5-1m.

[0019] Furthermore, the specific operation steps of the biogas slurry oxidation in step (4) are as follows: the biogas slurry is oxidized with 5wt% H2O2, after standing and filtering, the pH is adjusted to less than 6.5 with H2SO4.

[0020] The oxidized filtered biogas is adjusted to pH < 6.5 and then sprayed from the top of the scrubber. Ammonia, the main gas of odor in the breeding stage, dissolves in the acidic biogas to become ammonium ions. The acidic biogas passes through the packing layer and then forms struvite precipitates on the surface of the carbon-rich porous material. Specifically, the preparation of MgO slow-release material can dissolve magnesium ions, and the carbon-rich porous material has a high specific surface area and strong adsorption, so it can adsorb ammonium ions and phosphate ions in the biogas slurry, and then combine with the dissolved magnesium ions to form struvite precipitates, thereby removing ammonia in the biogas slurry. However, if the biochar loaded with magnesium oxide is used directly, when the biogas slurry passes through the packing layer, part of the ammonium ions and phosphate ions in the biogas slurry react with the magnesium ions on the biochar to form struvite precipitates attached to the surface of the biochar, reducing the release efficiency of magnesium ions, thereby affecting the treatment of odor. Therefore, the present invention covers the surface of biochar with a polymer film and improves the polymer film at the same time, thereby reducing the adsorption of ammonium ions and phosphate ions by the MgO slow-release material, and instead adsorbing them into the pores of the carbon-rich porous material, thereby avoiding the precipitation of struvite on the surface of the MgO slow-release material.

[0021] Therefore, when carrying out biochar loading polymer film, stearic acid is added, which can react with the hydroxyl group in polyvinyl alcohol, thereby reducing the water absorption of the polymer film, preventing the polymer film from swelling and breaking due to water absorption, improving the stability of the polymer film, avoiding the MgO slow-release material surface from exposing the internal biochar, and competing with the carbon-rich porous material to adsorb the ammonium ions and phosphate ions in the biogas slurry and form struvite precipitation with the magnesium ions. At the same time, polyvinyl alcohol is easily soluble under acidic conditions, so it is necessary to improve the stability of polyvinyl alcohol to prevent the polymer film from dissolving and leaking internal particles during the treatment of biogas slurry, so the present invention adds β-cyclodextrin, which interacts with polyvinyl alcohol, further increases the stability of the polymer film, and prevents the polyvinyl alcohol from gradually dissolving under acidic conditions and exposing the internal biochar; at the same time, due to the micropores of β-cyclodextrin cyclodextrin itself, the polymer film has a pore-forming effect, thereby increasing the diffusion capacity of magnesium ions and promoting the outward release of magnesium ions; in addition, β-cyclodextrin can also cooperate with glucose to increase the supersaturation of crystallization, slowing down the crystal growth rate, thereby hindering the growth of crystals. When biochar is loaded on the polymer film, citric acid is added to react with polyvinyl alcohol to improve the stability of the polyvinyl alcohol after film formation, thereby improving the stability of the polymer film on the surface of the MgO slow-release material, avoiding exposure of the internal biochar, and adsorbing ammonium ions and phosphate ions in the biogas slurry to form struvite precipitation on the surface of the MgO slow-release material; the pH of the polymer film is adjusted to 6-6.5, and citric acid can be used to make the polymer film acidic, and struvite is not easy to form and precipitate on the surface of the MgO slow-release material, further inhibiting the precipitation of struvite on the surface of the MgO slow-release material.

[0022] Beneficial effects:

[0023] The present invention improves the polymer film on the surface of the MgO slow-release material, which can effectively reduce the attachment of struvite generated during the odor treatment process to the MgO slow-release material, and prevent the struvite from clogging the MgO slow-release material, so as to ensure the continuous release of magnesium ions and improve the working efficiency of the odor treatment. At the same time, the struvite generated during the odor treatment process is a high-quality slow-release fertilizer. Therefore, the present invention realizes the recycling of nitrogen and phosphorus in the breeding process while achieving efficient removal of odor from the farm. BRIEF DESCRIPTION OF THE DRAWINGS

[0024] Figure 1 : It is an odor treatment device. DETAILED DESCRIPTION

[0025] The present invention will be described in detail below with reference to specific embodiments:

[0026] Embodiment 1:

[0027] (1) Preparation of MgO slow-release material: The straw was crushed and mixed with MgCl2·6H2O solution at a mass volume ratio of 1kg:10L, and then a solution of NaCO3 and NaOH at a mass ratio of 1:1 was added to adjust the pH to 11. The mixture was stirred for 2 h in a stirrer and then allowed to stand for 1 day. The solid and liquid phases were dried and ground again, and extruded to obtain particles with a particle size of 1 cm. The particles were transferred to a biochar preparation machine and carbonized at 550°C for 2 h in the absence of oxygen. After cooling to room temperature, biochar particles were obtained.

[0028] 20g of polyvinyl alcohol was added to 1000ml of water, heated and stirred until completely dissolved to obtain a polyvinyl alcohol solution; 4g of stearic acid was added to 10ml of anhydrous ethanol, heated and stirred until completely dissolved to obtain a stearic acid solution; the polyvinyl alcohol solution and the stearic acid solution were mixed evenly, stirred at 85°C for 2h, and then 10g of β-cyclodextrin, 4g of glucose, and 10g of 1wt% citric acid solution were added, stirred at 50°C for 2h, cooled to room temperature, and then the pH was adjusted to 6 using a citric acid solution to obtain Mixed solution; 30g hydroxypropyl methylcellulose, 8g polyethylene glycol, 7g talc, 25g titanium dioxide and the mixed solution are mixed evenly to obtain a mixed material, the mixed material is mixed with anhydrous ethanol at a mass ratio of 1:40, stirred for 40min at room temperature with a magnetic stirrer, ultrasonicated at room temperature for 15min, and then mixed with the biochar particles prepared above at a mass ratio of 5:1 of the mixed material to the biochar particles, dried in a constant temperature incubator at 40°C for 5h and then taken out to obtain a MgO sustained-release material;

[0029] (2) Preparation of carbon-rich porous material: The straw was crushed, sieved, dried, and immersed in concentrated phosphoric acid. The mass ratio of the material to the concentrated phosphoric acid was 1:3. The straw was taken out and dried again, and then pyrolyzed at 800°C for 2h. After cooling to room temperature, it was rinsed with deionized water until the filtrate was neutral to obtain a carbon-rich porous material.

[0030] (3) Setting up the odor treatment device: The prepared MgO slow-release material and the carbon-rich porous material are filled, the upper layer of the filler is the MgO slow-release material, accounting for 10% of the total thickness of the filler, and the lower layer of the filler is a mixture of the MgO slow-release material and the carbon-rich porous material in a mass ratio of 2:10, and then the filler is filled into the scrubber to obtain the odor treatment device, and the filler height is 0.5m;

[0031] (4) Odor treatment: The biogas slurry is oxidized with 5 wt% H2O2, allowed to stand and filtered, and the pH value is adjusted to 6.3 with H2SO4. The oxidized biogas slurry is then sprayed down from the top of the odor treatment device. The odor is then introduced into the bottom of the odor treatment device through an exhaust device for odor treatment. After the treatment, the filler is recovered.

[0032] Embodiment 2:

[0033] (1) Preparation of MgO slow-release material: The straw was crushed and mixed with MgCl2·6H2O solution at a mass volume ratio of 1kg:10L, and then a solution of NaCO3 and NaOH at a mass ratio of 1:1 was added to adjust the pH to 11. The mixture was stirred for 2 h in a stirrer and then allowed to stand for 1 day. The solid and liquid phases were dried and ground again, and extruded to obtain particles with a particle size of 1.2 cm. The particles were transferred to a biochar preparation machine and carbonized at 550°C for 2 h in the absence of oxygen. After cooling to room temperature, biochar particles were obtained.

[0034] 21g of polyvinyl alcohol was added to 1050ml of water, heated and stirred until completely dissolved to obtain a polyvinyl alcohol solution; 4.4g of stearic acid was added to 11ml of anhydrous ethanol, heated and stirred until completely dissolved to obtain a stearic acid solution; the polyvinyl alcohol solution and the stearic acid solution were mixed evenly, stirred at 88°C for 2.3h, and then 11g of β-cyclodextrin, 4.4g of glucose, and 12g of 1wt% citric acid solution were added, stirred at 52°C for 2.3h, cooled to room temperature, and then the pH was adjusted to 6.3 with citric acid solution. , obtaining a mixed solution; 31 g of hydroxypropyl methylcellulose, 9 g of polyethylene glycol, 7.5 g of talc, 26.5 g of titanium dioxide, and the mixed solution were uniformly mixed to obtain a mixed material, the mixed material was mixed with anhydrous ethanol at a mass ratio of 1:40, stirred for 45 min at room temperature with a magnetic stirrer, ultrasonicated at room temperature for 18 min, and then mixed with the biochar particles prepared above at a mass ratio of 5:1 of the mixed material to the biochar particles, dried in a constant temperature incubator at 45°C for 5 h, and then taken out to obtain a MgO sustained-release material;

[0035] (2) Preparation of carbon-rich porous material: The straw was crushed, sieved, dried, and immersed in concentrated phosphoric acid. The mass ratio of the material to the concentrated phosphoric acid was 1:3. The straw was taken out and dried again, and then pyrolyzed at 830°C for 2h. After cooling to room temperature, it was rinsed with deionized water until the filtrate was neutral to obtain a carbon-rich porous material.

[0036] (3) Setting up the odor treatment device: The prepared MgO slow-release material and the carbon-rich porous material are filled, the upper layer of the filler is the MgO slow-release material, accounting for 15% of the total thickness of the filler, and the lower layer of the filler is a mixture of the MgO slow-release material and the carbon-rich porous material in a mass ratio of 2.5:10, and then the filler is filled into the scrubber to obtain the odor treatment device, and the filler height is 0.5m;

[0037] (4) Odor treatment: The biogas slurry is oxidized with 5 wt% H2O2, allowed to stand and filtered, and the pH value is adjusted to 6.2 with H2SO4. The oxidized biogas slurry is then sprayed from the top of the odor treatment device. The odor is then introduced from the bottom of the odor treatment device using an exhaust device for odor treatment. After the treatment, the filler is recovered.

[0038] Embodiment 3:

[0039] (1) Preparation of MgO slow-release material: The straw was crushed and mixed with MgCl2·6H2O solution at a mass volume ratio of 1kg:10L, and then a solution of NaCO3 and NaOH at a mass ratio of 1:1 was added to adjust the pH to 11. The mixture was stirred for 2 h in a stirrer and then allowed to stand for 1 day. The solid and liquid phases were dried and ground again, and extruded to obtain particles with a particle size of 1.5 cm. The particles were transferred to a biochar preparation machine and carbonized at 550°C for 2 h in the absence of oxygen. After cooling to room temperature, biochar particles were obtained.

[0040] 22g of polyvinyl alcohol was added to 1100ml of water, heated and stirred until completely dissolved to obtain a polyvinyl alcohol solution; 4.8g of stearic acid was added to 12ml of anhydrous ethanol, heated and stirred until completely dissolved to obtain a stearic acid solution; the polyvinyl alcohol solution and the stearic acid solution were mixed evenly, stirred at 90°C for 3h, and then 12g of β-cyclodextrin, 5.2g of glucose, and 15g of 1wt% citric acid solution were added, stirred at 55°C for 3h, cooled to room temperature, and then the pH was adjusted to 6.3 using a citric acid solution. Obtain a mixed solution; 32 g of hydroxypropyl methylcellulose, 108 g of polyethylene glycol, 8 g of talc, 28 g of titanium dioxide, and the mixed solution are uniformly mixed to obtain a mixed material, the mixed material is mixed with anhydrous ethanol at a mass ratio of 1:40, stirred for 50 min at room temperature with a magnetic stirrer, ultrasonicated at room temperature for 20 min, and then mixed with the biochar particles prepared above at a mass ratio of 5:1 of the mixed material to the biochar particles, dried in a constant temperature incubator at 45°C for 6 h, and then taken out to obtain a MgO sustained-release material;

[0041] (2) Preparation of carbon-rich porous material: The straw was crushed, sieved, dried, and immersed in concentrated phosphoric acid. The mass ratio of the material to the concentrated phosphoric acid was 1:3. The straw was taken out and dried again, and then pyrolyzed at 850°C for 2h. After cooling to room temperature, it was rinsed with deionized water until the filtrate was neutral to obtain a carbon-rich porous material.

[0042] (3) Setting up the odor treatment device: The prepared MgO slow-release material and the carbon-rich porous material are filled, the upper layer of the filler is the MgO slow-release material, accounting for 20% of the total thickness of the filler, and the lower layer of the filler is a mixture of the MgO slow-release material and the carbon-rich porous material in a mass ratio of 3:10, and then the filler is filled into the scrubber to obtain the odor treatment device, and the filler height is 0.5m;

[0043] (4) Odor treatment: The biogas slurry is oxidized with 5 wt% H2O2, allowed to stand and filtered, and the pH value is adjusted to 6.3 with H2SO4. The oxidized biogas slurry is then sprayed down from the top of the odor treatment device. The odor is then introduced into the bottom of the odor treatment device through an exhaust device for odor treatment. After the treatment, the filler is recovered.

[0044] Comparative Example 1:

[0045] This comparative example is compared with Example 1, the only difference is that the polymer film raw material of the biochar is different, specifically, no stearic acid is added, and the specific method is as follows:

[0046] (1) Preparation of MgO slow-release material: The straw was crushed and mixed with MgCl2·6H2O solution at a mass volume ratio of 1kg:10L, and then a solution of NaCO3 and NaOH at a mass ratio of 1:1 was added to adjust the pH to 11. The mixture was stirred for 2 h in a stirrer and then allowed to stand for 1 day. The solid and liquid phases were dried and ground again, and extruded to obtain particles with a particle size of 1 cm. The particles were transferred to a biochar preparation machine and carbonized at 550°C for 2 h in the absence of oxygen. After cooling to room temperature, biochar particles were obtained.

[0047] 20g of polyvinyl alcohol was added to 1000ml of water, heated and stirred until completely dissolved to obtain a polyvinyl alcohol solution; then 10g of β-cyclodextrin, 4g of glucose, and 10g of 1wt% citric acid solution were added to the polyvinyl alcohol solution, stirred at 50°C for 2h, cooled to room temperature, and the pH was adjusted to 6 with a citric acid solution to obtain a mixed solution; 30g of hydroxypropyl methylcellulose, 8g of polyethylene glycol, 7g of talcum powder, 25g of titanium dioxide, and the mixed solution were mixed uniformly to obtain a mixed material, the mixed material was mixed with anhydrous ethanol at a mass ratio of 1:40, stirred at room temperature for 40min with a magnetic stirrer, and ultrasonicated at room temperature for 15min, and then mixed with the biochar particles prepared above at a mass ratio of 5:1, and dried at 40°C in a constant temperature incubator for 5h to obtain a MgO sustained-release material;

[0048] (2)-(4) are the same as in Example 1.

[0049] Comparative Example 2:

[0050] This comparative example is compared with Example 1, the only difference is that the polymer film raw material of the biochar is different, specifically, no β-cyclodextrin is added, and the specific method is as follows:

[0051] (1) Preparation of MgO slow-release material: The straw was crushed and mixed with MgCl2·6H2O solution at a mass volume ratio of 1kg:10L, and then a solution of NaCO3 and NaOH at a mass ratio of 1:1 was added to adjust the pH to 11. The mixture was stirred for 2 h in a stirrer and then allowed to stand for 1 day. The solid and liquid phases were dried and ground again, and extruded to obtain particles with a particle size of 1 cm. The particles were transferred to a biochar preparation machine and carbonized at 550°C for 2 h in the absence of oxygen. After cooling to room temperature, biochar particles were obtained.

[0052] 20g of polyvinyl alcohol was added to 1000ml of water, heated and stirred until completely dissolved to obtain a polyvinyl alcohol solution; 4g of stearic acid was added to 10ml of anhydrous ethanol, heated and stirred until completely dissolved to obtain a stearic acid solution; the polyvinyl alcohol solution and the stearic acid solution were mixed evenly, stirred at 85°C for 2h, and then 4g of glucose and 10g of 1wt% citric acid solution were added, stirred at 50°C for 2h, cooled to room temperature, and the pH was adjusted to 6 with a citric acid solution to obtain a mixed solution; 30g of hydroxypropyl methylcellulose, 8g of polyethylene glycol, 7g of talcum powder, 25g of titanium dioxide, and the mixed solution were mixed evenly to obtain a mixed material, the mixed material was mixed with anhydrous ethanol at a mass ratio of 1:40, stirred at room temperature for 40min with a magnetic stirrer, and ultrasonicated at room temperature for 15min, and then mixed with the above-prepared biochar particles at a mass ratio of 5:1, dried at 40°C in a constant temperature incubator for 5h, and then taken out to obtain a MgO sustained-release material;

[0053] (2)-(4) are the same as in Example 1.

[0054] Comparative Example 3:

[0055] This comparative example is compared with Example 1, the only difference is that the polymer film raw material of biochar is different, specifically, no glucose is added, and the specific method is as follows:

[0056] (1) Preparation of MgO slow-release material: The straw was crushed and mixed with MgCl2·6H2O solution at a mass volume ratio of 1kg:10L, and then a solution of NaCO3 and NaOH at a mass ratio of 1:1 was added to adjust the pH to 11. The mixture was stirred for 2 h in a stirrer and then allowed to stand for 1 day. The solid and liquid phases were dried and ground again, and extruded to obtain particles with a particle size of 1 cm. The particles were transferred to a biochar preparation machine and carbonized at 550°C for 2 h in the absence of oxygen. After cooling to room temperature, biochar particles were obtained.

[0057] 20g of polyvinyl alcohol was added to 1000ml of water, heated and stirred until completely dissolved to obtain a polyvinyl alcohol solution; 4g of stearic acid was added to 10ml of anhydrous ethanol, heated and stirred until completely dissolved to obtain a stearic acid solution; the polyvinyl alcohol solution and the stearic acid solution were mixed evenly, stirred at 85°C for 2h, and then 10g of β-cyclodextrin and 10g of 1wt% citric acid solution were added, stirred at 50°C for 2h, cooled to room temperature, and the pH was adjusted to 6 with a citric acid solution to obtain a mixed solution; 30g of hydroxypropyl methylcellulose, 8g of polyethylene glycol, 7g of talcum powder, 25g of titanium dioxide, and the mixed solution were mixed evenly to obtain a mixed material, the mixed material was mixed with anhydrous ethanol at a mass ratio of 1:40, stirred at room temperature for 40min with a magnetic stirrer, and ultrasonicated at room temperature for 15min, and then mixed with the above-prepared biochar particles at a mass ratio of 5:1, dried at 40°C in a constant temperature incubator for 5h, and then taken out to obtain a MgO sustained-release material;

[0058] (2)-(4) are the same as in Example 1.

[0059] Comparative Example 4:

[0060] This comparative example is compared with Example 1, the only difference is that the polymer film raw material of the biochar is different, specifically, no citric acid is added, and the specific method is as follows:

[0061] (1) Preparation of MgO slow-release material: The straw was crushed and mixed with MgCl2·6H2O solution at a mass volume ratio of 1kg:10L, and then a solution of NaCO3 and NaOH at a mass ratio of 1:1 was added to adjust the pH to 11. The mixture was stirred for 2 h in a stirrer and then allowed to stand for 1 day. The solid and liquid phases were dried and ground again, and extruded to obtain particles with a particle size of 1 cm. The particles were transferred to a biochar preparation machine and carbonized at 550°C for 2 h in the absence of oxygen. After cooling to room temperature, biochar particles were obtained.

[0062] 20g of polyvinyl alcohol was added to 1000ml of water, heated and stirred until completely dissolved to obtain a polyvinyl alcohol solution; 4g of stearic acid was added to 10ml of anhydrous ethanol, heated and stirred until completely dissolved to obtain a stearic acid solution; the polyvinyl alcohol solution and the stearic acid solution were mixed evenly, stirred at 85°C for 2h, and then 10g of β-cyclodextrin and 4g of glucose were added, stirred at 50°C for 2h, cooled to room temperature, and the pH was adjusted to 6 with a hydrochloric acid solution to obtain a mixed solution; 30g of hydroxypropyl methylcellulose, 8g of polyethylene glycol, 7g of talcum powder, 25g of titanium dioxide, and the mixed solution were mixed evenly to obtain a mixed material, the mixed material was mixed with anhydrous ethanol at a mass ratio of 1:40, stirred at room temperature for 40min with a magnetic stirrer, and ultrasonicated at room temperature for 15min, and then mixed with the above-prepared biochar particles at a mass ratio of 5:1, dried at 40°C in a constant temperature incubator for 5h, and then taken out to obtain a MgO sustained-release material;

[0063] (2)-(4) are the same as in Example 1.

[0064] Comparative Example 5:

[0065] This comparative example is compared with Example 1, and the only difference is that the preparation method of the polymer film of biochar is different, specifically, the pH is not adjusted, and the specific method is as follows:

[0066] (1) Preparation of MgO slow-release material: The straw was crushed and mixed with MgCl2·6H2O solution at a mass volume ratio of 1kg:10L, and then a solution of NaCO3 and NaOH at a mass ratio of 1:1 was added to adjust the pH to 11. The mixture was stirred for 2 h in a stirrer and then allowed to stand for 1 day. The solid and liquid phases were dried and ground again, and extruded to obtain particles with a particle size of 1 cm. The particles were transferred to a biochar preparation machine and carbonized at 550°C for 2 h in the absence of oxygen. After cooling to room temperature, biochar particles were obtained.

[0067] 20g of polyvinyl alcohol was added to 1000ml of water, heated and stirred until completely dissolved to obtain a polyvinyl alcohol solution; 4g of stearic acid was added to 10ml of anhydrous ethanol, heated and stirred until completely dissolved to obtain a stearic acid solution; the polyvinyl alcohol solution and the stearic acid solution were mixed evenly, stirred at 85°C for 2h, and then 10g of β-cyclodextrin, 4g of glucose, and 10g of 1wt% citric acid solution were added, stirred at 50°C for 2h, and cooled to room temperature to obtain a mixed solution; 30g of hydroxypropyl methylcellulose, 8g of polyethylene glycol, 7g of talcum powder, 25g of titanium dioxide, and the mixed solution were mixed evenly to obtain a mixed material, the mixed material was mixed with anhydrous ethanol at a mass ratio of 1:40, stirred at room temperature for 40min with a magnetic stirrer, and ultrasonicated at room temperature for 15min, and then mixed with the above-prepared biochar particles at a mass ratio of 5:1, dried at 40°C in a constant temperature incubator for 5h, and then taken out to obtain a MgO sustained-release material;

[0068] (2)-(4) are the same as in Example 1.

[0069] Comparative Example 6:

[0070] This comparative example is compared with Example 1, and the only difference is that the biochar coating method is different, specifically, the polymer film is not treated, and the specific method is as follows:

[0071] (1) Preparation of MgO slow-release material: The straw was crushed and mixed with MgCl2·6H2O solution at a mass volume ratio of 1kg:10L, and then a solution of NaCO3 and NaOH at a mass ratio of 1:1 was added to adjust the pH to 11. The mixture was stirred for 2 h in a stirrer and then allowed to stand for 1 day. The solid and liquid phases were dried and ground again, and extruded to obtain particles with a particle size of 1 cm. The particles were transferred to a biochar preparation machine and carbonized at 550°C for 2 h in the absence of oxygen. After cooling to room temperature, biochar particles were obtained.

[0072] 30 g of hydroxypropyl methylcellulose, 20 g of polyvinyl alcohol, 8 g of polyethylene glycol, 7 g of talc and 25 g of titanium dioxide were uniformly mixed to obtain a mixed material, the mixed material was mixed with anhydrous ethanol at a mass ratio of 1:40, stirred for 40 min at room temperature with a magnetic stirrer, ultrasonicated at room temperature for 15 min, and then mixed with the biochar particles prepared above at a mass ratio of 5:1, and dried in a constant temperature incubator at 40°C for 5 h before taking out;

[0073] (2)-(4) are the same as in Example 1.

[0074] experiment:

[0075] Odor treatment device setting: The odor treatment device is 3m high, 1.5m in diameter, and 0.5m in height. The prepared MgO slow-release material and carbon-rich porous material are filled. The upper layer of the material is MgO slow-release material, accounting for 10% of the total thickness of the filler. The lower layer of the filler is a mixture of MgO slow-release material and carbon-rich porous material in a mass ratio of 2:10. Then the filler is filled into the scrubber to obtain the odor treatment device. The empty tower gas flow rate is 1.5m / s, and the spray density is 1m 3 / (m 2 h);

[0076] Odor treatment: The prepared biogas slurry is sprayed down from the top of the odor treatment device, and then the odor is introduced into the bottom of the odor treatment device through the exhaust device for odor treatment.

[0077] According to the above method, the following experiments were performed:

[0078] 1. Experimental group 1 used the MgO sustained-release material and carbon-rich porous material prepared by the method of Example 1;

[0079] 2. Comparative groups 1-6 used the MgO sustained-release materials prepared in Comparative Examples 1-6 and the carbon-rich porous material prepared in Example 1.

[0080] 3. Preparation of biogas slurry: Sodium phosphate was used to prepare simulated biogas slurry so that the phosphate ion content in the biogas slurry was 500 mg / L, and H2SO4 was used to adjust the pH of the biogas slurry to 6;

[0081] 4. Mix ammonia and air in a volume ratio of 2:1 to simulate the odor and pass it into the odor treatment device;

[0082] 5. Each group processes 1m 3 The treated biogas slurry was collected and the content of phosphate ions in the biogas slurry was detected, and the phosphate ion consumption was calculated. The results are shown in Table 1.

[0083] Table 1

[0084]

[0085]

[0086] Analyzing Table 1, we can get:

[0087] 1. Compared with experimental group 1, in comparison group 1, stearic acid was not added, and the polymer film on the surface of the MgO slow-release material was easily swelled and ruptured due to water absorption, resulting in the exposure of the internal biochar on the surface of the MgO slow-release material to adsorb ammonium ions and phosphate ions in the biogas slurry and magnesium ions in the MgO slow-release material to form struvite precipitation, which would block the surface of the MgO slow-release material and hinder the release of magnesium ions, thereby reducing the reaction efficiency of struvite and reducing the number of phosphate ions participating in the reaction in the biogas slurry. Therefore, the phosphate consumption in comparison group 1 was less, which in turn led to a decrease in the odor treatment efficiency and a low recovery efficiency of nitrogen and phosphorus in the biogas slurry.

[0088] 2. Compared with experimental group 1, control group 2 did not add β-cyclodextrin. The polymer film on the surface of the MgO slow-release material was easily dissolved in an acidic environment, resulting in the exposure of the internal biochar and the adsorption of ammonium ions and phosphate ions to form struvite precipitation on the surface of the MgO slow-release material, resulting in the blockage of the surface of the MgO slow-release material, the release efficiency of magnesium ions was reduced, and the reaction of struvite was affected; and β-cyclodextrin can play a pore-forming role on the polymer film, thereby increasing the release efficiency of magnesium ions. Therefore, the struvite reaction efficiency of control group 2 without adding β-cyclodextrin is low, and the amount of phosphate ions consumed is low. In addition, β-cyclodextrin can also inhibit the formation of struvite crystals, so the struvite reaction efficiency of control group 2 without adding β-cyclodextrin is further reduced, and the amount of phosphate ions consumed is reduced. Compared with experimental group 1, control group 3 did not add glucose, and the growth rate of struvite crystals on the surface of MgO slow-release material was faster, which led to blockage of the surface of MgO slow-release material, reduced magnesium ion release efficiency, and hindered the continued precipitation of struvite. Therefore, the phosphate ions in the biogas slurry could not continue to be consumed, and the final consumption of phosphate ions was low.

[0089] 3. Compared with experimental group 1, control group 4 did not add citric acid, and the stability of the polymer membrane was lower. The exposure of the internal biochar caused the MgO slow-release material to easily absorb ammonium ions and phosphate ions to form struvite precipitation on the surface of the MgO slow-release material, which hindered the release of magnesium ions, affected the struvite reaction, and reduced the actual amount of phosphate ions consumed.

[0090] 4. Compared with experimental group 1, control group 5 did not adjust the pH, and the consumption of phosphate ions was lower. This is because struvite is not easy to form in an acidic environment. In control group 5, the pH was not adjusted, and struvite precipitation was easily formed on the surface of the MgO slow-release material, which hindered the release of magnesium ions and thus hindered the struvite reaction.

[0091] 5. Compared with experimental group 1, control group 6 did not treat the polymer membrane, and the generated struvite precipitate was easy to adhere to the surface of MgO sustained-release material, hindering the continued release of magnesium ions, resulting in the struvite reaction being affected, and thus the phosphate ion consumption was reduced.

[0092] The above embodiments are only used to illustrate the technical solutions of the present invention and are not intended to limit the present invention. Although the present invention is described in detail with reference to the preferred embodiments, it should be understood by those skilled in the art that the technical solutions of the present invention may be modified or replaced by equivalents without departing from the purpose and scope of the technical solutions of the present invention, which should be included in the scope of the claims of the present invention. The techniques, shapes, and structural parts not described in detail in the present invention are all known technologies.

Claims

1. A method for treating odor in a breeding farm, characterized in that: The method comprises the following steps: (1) Preparation of MgO slow-release material: Crush the crop straw and mix it evenly with 1.0 mol / L MgCl2·6H2O, then adjust the pH to 10.0, stir and react, let it stand for 24 h, dry the solid-liquid mixture, grind it, extrude it to obtain particles, carbonize the particles to obtain biochar, and then load a layer of polymer membrane on the surface of the biochar to obtain MgO slow-release material; (2) Preparation of carbon-rich porous materials: The high-lignin content material was crushed, sieved, dried, and immersed in concentrated phosphoric acid. The mass ratio of the material to the concentrated phosphoric acid was 1:

3. The material was taken out and dried again, and then pyrolyzed at 800-850°C for 2h. After cooling to room temperature, it was rinsed with deionized water until the filtrate was neutral to obtain a carbon-rich porous material. (3) Setting up an odor treatment device: Filling the prepared MgO slow-release material and carbon-rich porous material into a scrubbing tower to obtain an odor treatment device; (4) Odor treatment: The oxidized biogas slurry is sprayed down from the top of the odor treatment device, and then the odor is introduced into the bottom of the odor treatment device through the exhaust device for odor treatment. After the treatment, the filler is recovered.

2. The method for treating farm odor according to claim 1, characterized in that: The method for loading the biochar with a polymer membrane in step (1) is as follows: S1: adding polyvinyl alcohol to water, heating and stirring until completely dissolved to obtain a polyvinyl alcohol solution; adding stearic acid to anhydrous ethanol, heating and stirring until completely dissolved to obtain a stearic acid solution; mixing the polyvinyl alcohol solution and the stearic acid solution evenly, stirring at 85-90° C. for 2-3 h, then adding β-cyclodextrin, glucose, and 1wt% citric acid solution, stirring at 50-55° C. for 2-3 h, cooling to room temperature, and adjusting the pH to 6-6.5 to obtain a mixed solution; S2: Evenly mix hydroxypropyl methylcellulose, polyethylene glycol, talc, titanium dioxide and the mixed solution to obtain a mixed material, mix the mixed material with anhydrous ethanol in a mass ratio of 1:40, stir with a magnetic stirrer at room temperature for 40-50 minutes, ultrasonicate at room temperature for 15-20 minutes, then mix it with biochar particles, dry it at 40-45°C for 5-6 hours and take it out.

3. A method for treating farm odor according to claim 3, characterized in that: In the method for loading the biochar with a polymer membrane, the mass ratios of hydroxypropyl methylcellulose, polyvinyl alcohol, polyethylene glycol, talc and titanium dioxide are (30-32):(20-22):(8-10):(7-8):(25-28).

4. The method for treating farm odor according to claim 4, characterized in that: In step S1 of the method for loading polymer membrane with biochar, the mass ratio of polyvinyl alcohol, stearic acid, β-cyclodextrin, glucose and 1 wt% citric acid solution is (5-6): (1-1.2): (2.5-3): (1-1.3): (10-15).

5. The method for treating farm odor according to claim 4, characterized in that: In the step (1), the crop straw is crushed to a particle size of less than 0.25 mm, and the crushed crop straw and the MgCl2·6H2O solution are mixed in a volume-to-mass ratio of 1 kg:10 L.

6. The method for treating farm odor according to claim 5, characterized in that: In the step (1), the extrusion molding obtains particles with a particle size of 1-1.5 cm.

7. A method for treating farm odor according to claim 6, characterized in that: The filler in step (3) is composed of two layers. The upper layer of the filler is MgO slow-release material, accounting for 10-20% of the total thickness of the filler, and the lower layer of the filler is a mixture of MgO slow-release material and carbon-rich porous material in a mass ratio of (2-3):

10. The filler height is usually 0.5-1m.

8. The method for treating farm odor according to claim 7, characterized in that: The specific operation steps of the biogas slurry oxidation in step (4) are as follows: the biogas slurry is oxidized with 5wt% H2O2, and after standing and filtering, the pH is adjusted to <6.5 with H2SO4.

Citation Information

Cited By

  • Method for deodorizing sheep manure compost by using modified charcoal loaded electrolyte

    CN122482877A